Analysis of the global shipping traffic for the feasibility of a structural recovery program of Argo floats - González-Santana, Alberto; Oosterbaan, Marijn; Clavelle, Tyler; Maze, Guillaume; Notarstefano, Giulio; Poffa, Noe; Vélez-Belchí, Pedro (Frontiers in Marine Science, 2023)
The Argo observation network is made up of approximately 4,000 drifting floats, which provide valuable information about the ocean and its role in the climate system. Each one of these floats work in continuous cycles, until their batteries run out. Due to its importance in operational forecasting and climate research, the Argo community continually assesses the status of the sensors mounted on each of the floats. Recovering floats would offer a great opportunity to gain insight into sensor performance and stability, although the economic and environmental costs of dedicating a ship exclusively to recover Argo floats make it unsustainable. In this work, the potential of world shipping traffic as float retrievers has been evaluated through an analysis of encounters based on the Automatic Identification System (AIS) of ships and the location of Argo floats in the years 2019 and 2020. About 18,500 and 28,500 encounters happened for both years, respectively. The Mediterranean Sea hosted the most encounters, and fishing ships were the most suitable type of ship aimed for potential recoveries. A total of 298 and 373 floats interacted with the world shipping traffic in favorable weather conditions in 2019 and 2020, respectively, a figure equivalent to 25% of the annual replacement rate of the Argo network. The same approach was applied to 677 floats affected by abrupt salinity drift (ASD), an issue that has recently come to the attention of the Argo community. It turned out that 59 and 103 ASD-affected floats interacted with ships of opportunity in both years.